What is the optimal management of thromboprophylaxis after liver transplantation regarding prevention of bleeding, hepatic artery, or portal vein thrombosis? A systematic review of the literature and expert panel recommendations. Issue 10 (9th December 2022) - Kirchner, Varvara A.; O'Farrell, Bryan; Imber, Charles; McCormack, Lucas; Northup, Patrick G.; Song, Gi‐Won; Spiro, Michael; Raptis, Dimitri A.; Durand, François; ,
Abstract: Background: A key tenet of clinical management of patients post liver transplantation (LT) is the prevention of thrombotic and bleeding complications. This systematic review investigated the optimal management of thromboprophylaxis after LT regarding portal vein thrombosis (PVT) or hepatic artery thrombosis (HAT) and prevention of bleeding. Methods: Systematic review following PRISMA guidelines and recommendations using the GRADE approach derived from an international expert panel. Seven databases were used to conduct extensive literature searches focusing on the use of anticoagulation in LT and its impact on the following outcomes: PVT, HAT, and bleeding (CRD42021244288). Results: Of the 2478 articles/abstracts screened, 16 studies were included in the final review. All articles were critically appraised by a panel of independent reviewers. There was wide variation regarding the anticoagulation protocols used. Thromboprophylaxis with therapeutic doses of heparin/Vitamin K antagonist combination did not decrease the risk of de novo or the recurrence of PVT but was associated with an increased risk of bleeding in some studies. Only the use of aspirin resulted in a small but significant decrease in the incidence of HAT post‐LT, yet it did not increase the risk of bleeding. Conclusions: Based on existing data and expert opinion, thromboprophylaxis at therapeutic or prophylactic dose is not recommended for prevention of de novo PVT following LT in patients not at high risk. Aspirin should be considered as the standard of care following LT to prevent HAT. Thromboprophylaxis should be strongly considered in recipients at risk of HAT and PVT following LT.